Hubungan Kebiasaan Mengonsumsi Kopi Susu dan Kopi Hitam dengan Tekanan Darah - Dewajanti, Anna Maria; Pratiwi, Indah; Susilowati, Rina Priastini; Rumiati, Flora (Universitas Kristen Krida Wacana, 2024)
The habit of people who consume coffee will have an impact on increasing blood pressure, where if you drink 4 or more cups of coffee in one day, the systolic pressure will increase by approximately 10 mmHg and around 8 mmHg in diastolic blood pressure. The purpose of this study was to see the relationship between the habit of consuming milk coffee and black coffee with blood pressure in students of the Faculty of Medicine at Krida Wacana Christian University. This research used a cross-sectional approach with a population of 2020 Ukrida Faculty of Medicine students. The sample in this study was 102 people with a simple random sampling technique. It was found that the average 2020 Ukrida Faculty of Medicine student consumed coffee 1-2 times a day at a rate of 1-2 cups per day, but there were also some who consumed 3-4 cups of coffee a day. Data analysis used the Person Chi-Square and obtained the p-value for milk coffee: 0.126 and the p-value for black coffee: 0.656. So this shows that both milk coffee and black coffee have no significant relationship with an increase in blood pressure.